The Phenomenon of Generation Z's Loss of Appreciation for Original Literary Works: A Phenomenological Study of Adaptations - Aulia, Violla Dwi Tuti; Malik, Abdul; Dwi Leoni, Tessa; Elfitra, Legi; Lolita, Asri; Musliha, Musliha (Universitas Pahlawan Tuanku Tambusai, 2026)
The transformation of Indonesian literature in the digital era through adaptation shifts Generation Z's appreciation from original text-based works to digital adaptations such as films and podcasts, particularly for prospective literature educators at Raja Ali Haji Maritime University. This qualitative descriptive study using a phenomenological approach aims to describe the phenomenon of loss of appreciation among 10 Generation Z students (class of 2022) of the Indonesian Language and Literature Education Study Program through purposive sampling. In-depth interviews, participant observation, and documentation were analyzed via phenomenological reduction covering five aspects: aesthetic experience, subjective awareness, transformation of experience, interpretation of meaning, and the creator-audience relationship. The results show that Generation Z appreciates digital adaptations more due to their practicality, visual-audio entertainment, concrete experiences, simple interpretations, and the incompatibility of the packaging of original works with modern technology. In conclusion, adaptation significantly influences Generation Z's aesthetic awareness, recommending a blended digital-traditional pedagogy for the preservation of in-depth literary appreciation.